Comparative Analysis of Optimal Portfolio Formation Using the Single Index Model and Black-Litterman Model on a Fixed Sample of IDX30 Constituents - Widya Sari, Ida Ayu Artha; Harta Mimba, Ni Putu Sri (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study compares the Single Index Model and the Black-Litterman model in forming an optimal stock portfolio on a fixed sample of recurrent IDX30 constituents in order to assess differences in portfolio composition, return, risk, and risk-adjusted performance in the Indonesian capital market. This study compares the Single Index Model and the Black-Litterman model in forming an optimal stock portfolio on a fixed sample of recurrent IDX30 constituents in order to assess differences in portfolio composition, return, risk, and risk-adjusted performance in the Indonesian capital market. The Single Index Model produced a more diversified 9-stock portfolio and the stronger Sharpe ratio, while the Black-Litterman model produced a more concentrated 3-stock portfolio with higher expected return, higher Treynor ratio, and higher Jensen’s alpha. The results indicate that no single model dominates on all criteria. The Single Index Model is more favorable from the perspective of total-risk-adjusted efficiency, whereas the Black-Litterman model is more favorable from the perspective of return orientation and systematic-risk-adjusted performance. Future research should strengthen the economic justification of investor views and expand the benchmark comparison to broader Indonesian stock universes..